Petrochronology of polygenetic white micas (Naxos, Greece). (27th December 2022) - Villa, Igor M.; Glodny, Johannes; Peillod, Alexandre; Skelton, Alasdair; Ring, Uwe
Abstract: Naxos in the Greek Cyclades preserves a type example of polymetamorphism. The southern and northern parts of the island record different Tertiary P–T histories between Eocene and Miocene times, including a blueschist facies event, one or more amphibolite/greenschist facies overprint(s) and contact metamorphism. Age attributions for these events are inconsistent in the literature. Here, we propose a new approach that combines electron probe microanalyzer (EPMA) characterization of the white mica (WM) with 39 Ar‐ 40 Ar–Rb‐Sr multichronometry. Textural–petrographic–compositional observations reveal that the polygenetic WM consists of five different generations: pre‐Eocene relicts, paragonite, high‐Si phengite, low‐Si phengite and muscovite. EPMA mapping of four WM samples, previously analysed by Rb‐Sr, reveals major element compositions heterogeneous down to the μm scale. Each WM consists of chemically distinct generations, documenting submicron‐scale retrogression of high‐pressure (HP) phengite grains to muscovite. Four WM samples from a N‐S traverse across the island were analysed by 39 Ar‐ 40 Ar stepheating, comparing coarse and fine sieve size fractions to obtain overdetermined K‐Ar systematics. Fine sieve fractions are richer in Cl than coarse ones. Linear arrays in Cl/K‐age isotope correlation diagrams show two predominant WM generations (one Cl‐poor at ca. 38 Ma and one Cl‐rich at <20 Ma). A lower‐grade sample from southern Naxos was less pervasively recrystallized, provides older ages and preserves at least three WM generations, including a relict WM with a pre‐Palaeocene K‐Ar age, consistent with the high Ar retentivity of WM in the absence of complete recrystallization. The age of the Cl‐poor end‐member WM approximates the age of the HP event, 38 Ma. Ar inheritance in Cretaceous mica relicts is heterogeneous at the single‐grain scale. Comparing the degassing rates of the WM fractions rules out 'multidomain' diffusion. As no sample is monomineralic, the degassing rate of each polygenetic mica is instead controlled by the mass balanced sum of the unrelated rate constants of its constituent minerals. Given the commonness of zoned and composite micas, the approach detailed here is potentially useful for reconstructing polyphase metamorphic histories worldwide.